Pengukuran Kesadaran Keamanan Informasi Mahasiswa Aktif Pengguna Simak Menggunakan Human Aspects of Information Security Questionnaire - Matahari, Hari; Purwani, Fenny; Gunawan, Catur Eri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Academic Information System of Universitas Islam Negeri Raden Fatah Palembang serves as a key infrastructure supporting academic processes. However, user behavior indicates a low level of information security awareness. Issues such as forgotten passwords, logging in through others’ devices, unawareness of storing sensitive personal data, switching devices due to access spikes, and infrequent password changes increase the risk of cyber threats that may compromise data privacy. This study measures the information security awareness level of active users of the Academic Information System using the Human Aspects of Information Security Questionnaire (HAIS-Q), which comprises three dimensions—Knowledge, Attitude, and Behavior (KAB)—and seven subareas weighted through the Analytic Hierarchy Process (AHP). Data were collected through questionnaires distributed to active students of UIN Raden Fatah Palembang. The findings show that the overall level of information security awareness falls into the “adequate” category, with a score of 72.49%. These results underscore the need for improvement initiatives, including more comprehensive education on information security within the Academic Information System.